Commercial Screen‐Printed Gold Electrodes for the Detection and Quantification of Aminothiols in Human Plasma by Liquid Chromatography with Electrochemical Detection. Issue 3 (20th February 2014) - Cavanillas, Santiago; Serrano, Núria; Díaz‐Cruz, José Manuel; Ariño, Cristina; Esteban, Miquel
Abstract In order to show the possibilities of screen‐printed electrodes in HPLC detection, a method is presented for routine quantification of aminothiols in human plasma. It uses commercial gold screen‐printed electrodes and provides a rapid, simple and economical procedure with a disposable detector and without any additional electrode. By working at 98 : 2 (0.05 % trifluoroacetic acid: methanol) and 0.9 V, it allows us to determine cysteine (Cys), cysteinyl‐glycine (Cys‐Gly), and homocysteine (HCys) at μmol/L levels. The method was validated, and linearity range, detection and quantification limits, precision and accuracy were evaluated by external calibration and by using N‐acetylcysteine as internal standard, which exhibited better precision.